2022
DOI: 10.3389/fmicb.2022.860931
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Damage in COVID-19: SARS-CoV-2 Infection and Intestinal Thrombosis

Abstract: The intestinal tract, with high expression of angiotensin-converting enzyme 2 (ACE2), is a major site of extrapulmonary infection in COVID-19. During pulmonary infection, the virus enters the bloodstream forming viremia, which infects and damages extrapulmonary organs. Uncontrolled viral infection induces cytokine storm and promotes a hypercoagulable state, leading to systemic microthrombi. Both viral infection and microthrombi can damage the gut–blood barrier, resulting in malabsorption, malnutrition, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 107 publications
0
26
0
2
Order By: Relevance
“…However, these chips are not the only ones used for research on viral diseases. Given that COVID-19, as well as other coronaviruses, can affect several organs, including kidneys, and the gastrointestinal, cardiovascular and nervous systems [ 90 , 91 , 92 , 93 ], 3D models of other organs have been used. Bein et al [ 94 ] recently modeled an immunocompetent human Intestine-on-a-Chip to study enteric NL63 coronavirus infection and treatment, whereas Helms et al [ 95 ], using kidney organoids derived from pluripotent stem cells, showed that SARS-CoV-2 can directly infect and damage kidney tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, these chips are not the only ones used for research on viral diseases. Given that COVID-19, as well as other coronaviruses, can affect several organs, including kidneys, and the gastrointestinal, cardiovascular and nervous systems [ 90 , 91 , 92 , 93 ], 3D models of other organs have been used. Bein et al [ 94 ] recently modeled an immunocompetent human Intestine-on-a-Chip to study enteric NL63 coronavirus infection and treatment, whereas Helms et al [ 95 ], using kidney organoids derived from pluripotent stem cells, showed that SARS-CoV-2 can directly infect and damage kidney tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic colitis, a rare presentation of SARS-CoV-2 involvement in the colon, has been reported in some cases [138,[183][184][185]. Microscopic examination of these cases showed coagulative mucosal necrosis with crypt apoptosis and small vessel thrombosis, mainly noted in the submucosal vasculature [184].…”
Section: The Effects Of Covid-19 Infection On the Coagulation System ...mentioning
confidence: 97%
“…Besides, several lines of evidence support that intestinal infection by SARS-CoV-2 could occur via the bloodstream[ 19 , 26 ]. The virus replicating in pulmonary alveolar epithelial cells or in ciliary cells of the nasal cavity is capable of breaching the basement membrane and causing viremia[ 27 ]. The GI tract comprises an extended network of capillaries harboring vascular epithelial cells, which are potential targets of circulating SARS-CoV-2.…”
Section: Gi Involvement and The Mechanisms Of Intestinal Infection In...mentioning
confidence: 99%
“…The GI tract comprises an extended network of capillaries harboring vascular epithelial cells, which are potential targets of circulating SARS-CoV-2. Thereafter, the proliferating virus is released from the infected cells into the gut, where it can infect neighboring enterocytes or reenter the circulation to generate new cycles of infection[ 27 , 28 ].…”
Section: Gi Involvement and The Mechanisms Of Intestinal Infection In...mentioning
confidence: 99%
See 1 more Smart Citation